Tissue factor (coagulation factor III): a potential double-edge molecule to be targeted and re-targeted toward cancer - Seyed Esmaeil Ahmadi; Ashkan Shabannezhad; Amir Kahrizi; Armin Akbar; Seyed Mehrab Safdari; Taraneh Hoseinnezhad; Mohammad Zahedi; Soroush Sadeghi; Mahsa Golizadeh Mojarrad; Majid Safa (Biomarker Research, 2023)
Abstract Tissue factor (TF) is a protein that plays a critical role in blood clotting, but recent research has also shown its involvement in cancer development and progression. Herein, we provide an overview of the structure of TF and its involvement in signaling pathways that promote cancer cell proliferation and survival, such as the PI3K/AKT and MAPK pathways. TF overexpression is associated with increased tumor aggressiveness and poor prognosis in various cancers. The review also explores TF's role in promoting cancer cell metastasis, angiogenesis, and venous thromboembolism (VTE). Of note, various TF-targeted therapies, including monoclonal antibodies, small molecule inhibitors, and immunotherapies have been developed, and preclinical and clinical studies demonstrating the efficacy of these therapies in various cancer types are now being evaluated. The potential for re-targeting TF toward cancer cells using TF-conjugated nanoparticles, which have shown promising results in preclinical studies is another intriguing approach in the path of cancer treatment. Although there are still many challenges, TF could possibly be a potential molecule to be used for further cancer therapy as some TF-targeted therapies like Seagen and Genmab’s tisotumab vedotin have gained FDA approval for treatment of cervical cancer. Overall, based on the overviewed studies, this review article provides an in-depth overview of the crucial role that TF plays in cancer development and progression, and emphasizes the potential of TF-targeted and re-targeted therapies as potential approaches for the treatment of cancer.